Shirkah Contracts Fuqaha Perspectives and Their Application in Islamic Cooperatives - Moh. Asep Zakariya Ansori; Sofyan Al Hakim Sofyan; Iwan Setiawan Iwan (Sekolah Tinggi Ekonomi dan Perbankan Islam Mr. Sjafruddin Prawiranegara, 2023)
Shirkah is a contract of cooperation between two or more people in one capital, skills, or trust in a particular business with profit sharing based on the ratio, Shirkah is very important role in the economic growth of society. However, there are differences of opinion among fuqahâ regarding the types of shirkah that are permitted in Islam. This study discusses the fuqaha's views on the permissibility of the types of shirkah and their application in cooperatives from a theoretical and practical perspective through the study of some literature and observation of the application of these types in cooperatives. The method used in this research is a literature study that collects information from books, journals, and other sources related to shirkah contracts and cooperatives. The results show that the shirkah contract in the sharia cooperative business is a form of business that is in accordance with sharia principles. However, there are differences of opinion among fuqaha regarding the permissibility of the types of shirkah applied in the practice. Therefore, it is important for cooperative managers to understand these differences of opinion in order to choose the right type of shirkah that is in accordance with sharia principles. Keywords: Shirkah, Types of shirkah contracts, Cooperatives